FUNGSI BAHASA LANSKAP LINGUISTIK PULAU KAMBUNO KABUPATEN SINJAI (PERSPEKTIF LANDRY DAN BOURHIS 1997) - Megawati Rustan; Anshari Anshari; Nensilianti Nensilianti (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2023)
Landry and Bourhis's Linguistic Landscape Study in studying LL texts obtains two functions, namely an informational function and a symbolic function. The information function is a marker that distinguishes the geographical area of the population that gives the language to the name of the place. That is, language acts as a marker of the territory of the speaking community and a differentiator from other population areas. While the symbolic function is the presence or absence of a group's language on the street signboard which has an impact on the feeling of being part of that group. This study aims to describe the language function of the linguistic landscape found on Kambuno Island. This study uses a qualitative descriptive method obtained through observation, interviews, and documentation. The results of the study found five data with three symbolic functions each, two information functions. This is experiencing inequality because it is found that the community's mindset is still low regarding the role of linguistic landscapes in the community environment.